(untitled) (Journal of Scientific Research, 2023)
The Industrial, Scientific, and Medical (ISM) frequency spectrum is used by the Wireless Local Area Network (WLAN) for its operation. Due to a limited number of available channels for WLAN operation, frequency channel assignment becomes very difficult. In WLAN, the access points (APs) are widely deployed, and because they share the same frequency, they start interfering with each other and causing more energy consumption. So WLAN frequency channels should be managed and assigned carefully to increase the energy efficiency of the wireless network. This paper proposes an energy-efficient channel assignment algorithm (EECAA) to improve the performance of the network. The suggested approach improves the network’s energy efficiency in terms of global delay, packet data loss, and the count of data retransmissions. The extensive simulation study demonstrates that, when compared to the channel handoff scheme and D2MD channel allocation algorithm for various traffic and network conditions, the proposed EECAA method greatly increases network throughput.